2009
DOI: 10.1111/j.1742-7843.2008.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pharmacological and Safety Evaluation of Hematide™, a PEGylated Peptidic Erythropoiesis‐Stimulating Agent, in Rodents

Abstract: Abstract:Hematide TM is a synthetic peptide-based, PEGylated erythropoiesis-stimulating agent, which is being developed for the chronic treatment of anaemia associated with chronic renal failure. To support the safety of long-term dosing of chronic renal failure patients, a comprehensive toxicology programme was implemented including rat subchronic and chronic studies. Rats were administered 0, 0.1, 1 and 10 mg/kg of Hematide every 3 weeks for 3 months via subcutaneous injection or for 6 months via intravenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…Area under curve and maximum concentration was seen to be greater by intravenous than subcutaneous route in a rodent study projecting better bioavailability by intravenous route but this difference was not observed clinically 24,28 .…”
Section: Preclinical and Clinical Studies Of Peginesatidementioning
confidence: 90%
See 1 more Smart Citation
“…Area under curve and maximum concentration was seen to be greater by intravenous than subcutaneous route in a rodent study projecting better bioavailability by intravenous route but this difference was not observed clinically 24,28 .…”
Section: Preclinical and Clinical Studies Of Peginesatidementioning
confidence: 90%
“…The immune responses, which are observed in the repeat dose toxicity studies conducted with the currently marketed ESA, were not observed with peginesatide 28 . Antibodies to peginesatide were not found to cross-react with EPO and vice versa.…”
Section: Preclinical and Clinical Studies Of Peginesatidementioning
confidence: 93%
“…(Greaves and Faccini, 1992;O'Malley et al, 2005). Furthermore, unlike in rodents (Woodburn et al, 2009), EMH has not been shown to occur in monkeys administered peginesatide up to 20 mg/kg i.v. every 3 weeks for 9 months (Woodburn et al, 2008a,b).…”
Section: Discussionmentioning
confidence: 99%
“…administration and correlating the ADME properties with the pharmacological activity have been reported (Woodburn et al, 2012). The toxicologic assessment of peginesatide was also performed in both the rat (Woodburn et al, 2009) and the monkey (Woodburn et al, 2008a,b). The monkey and the rat are appropriate species for the nonclinical assessment of peginesatide based on pharmacological, toxicological, and pharmacokinetic (PK) considerations.…”
Section: Introductionmentioning
confidence: 99%
“…Phage display technology is a powerful tool in drug discovery, particularly for the identification of ligands with novel functions [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], however, its application range covers very diverse areas such as nanostructured electronics [26,27], agriculture [28], medical diagnosis [29] and neurobiology [30], just to mention few. The success of phage display can be credited to the fact that highly diverse libraries can be constructed allowing rapid isolation and identification of specific proteinaceous ligands for numerous types of macromolecular targets [6,31].…”
Section: Foundation Reviewmentioning
confidence: 99%